Potent inhibitory effect on human platelet aggregation of the aerial part of Canna edulis - Nguyen, Thi Van Anh; Bui, Duc Huy; Le, Hong Luyen (Vietnam Journal of Science and Technology, 2024)
Canna edulis Ker Gawl has been used in Vietnamese Traditional Medicine for the treatment of heart diseases with very limited scientific evidence. This study aimed to evaluate the inhibitory effect on human platelet aggregation of the aerial part of C. edulis. Aerial C. edulis was firstly macerated with methanol, and then fractionated with different solvents to obtain 3 fractions: n-hexane, ethyl acetate and aqueous extracts. The inhibitory effects on human platelet aggregation of extracts were evaluated via three parameters: percentage inhibition of platelet aggregation (%I), area under the aggregation curve (AUC) and aggregation slope, using two agonists adenosine diphosphate (ADP) and collagen. The results showed that all extracts significantly inhibited platelet aggregation in a dose-dependent manner for both agonists. Moreover, all extracts significantly decreased AUC and slope, indicating their antiaggregatory effects on both general aggregation and aggregation velocity. Among extracts, the ethyl acetate fraction exhibited the strongest effect regardless of agonists used (%I at 4 mg/mL, 99.2% for both ADP and collagen). The n-hexane fraction also had significant inhibitory effect but it was weaker than the others (p < 0.05). This is the first study to demonstrate the potent antiplatelet effect of the aerial part of C. edulis. This plant could be a potential natural source for searching novel antiplatelet agents and developing dietary supplements for management of cardiovascular diseases.